Identifying technology solutions to bring conservation into the innovation era. Issue 10 (2nd October 2019) - Iacona, Gwenllian; Ramachandra, Anurag; McGowan, Jennifer; Davies, Alasdair; Joppa, Lucas; Koh, Lian Pin; Fegraus, Eric; Game, Edward; Guillera‐Arroita, Gurutzeta; Harcourt, Rob; Indraswari, Karlina; Lahoz‐Monfort, José J; et al.
Abstract : Innovation has the potential to enable conservation science and practice to keep pace with the escalating threats to global biodiversity, but this potential will only be realized if such innovations are designed and developed to fulfill specific needs and solve well‐defined conservation problems. We propose that business‐world strategies for assessing the practicality of innovation can be applied to assess the viability of innovations, such as new technology, for addressing biodiversity conservation challenges. Here, we outline a five‐step, "lean start‐up" based approach for considering conservation innovation from a business‐planning perspective. Then, using three prominent conservation initiatives – Marxan (software), Conservation Drones (technology support), and Mataki (wildlife‐tracking devices) – as case studies, we show how considering proposed initiatives from the perspective of a conceptual business model can support innovative technologies in achieving desired conservation outcomes.